PENGARUH ARUS KAS, LIKUIDITAS, RENTABILITAS, UKURAN PERUSAHAAN DAN RISIKO PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Safariyan, Fuji; -, Zulbahridar; -, Susilatri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the effect of cash flow, liquidity, profitability, firm size and firm risk on dividend policy. The type of data used is the documentary. Documentary data in the form of financial statements such as balance sheet, income statement and cash flow statement. The data obtained from the Indonesia Stock Exchange (IDX) Pekanbaru. Population in this study were 130 manufactur companies listed in Indonesia Stock Exchange (IDX) with a sample of 17 companies during the years 2009 to 2012. Technique this study using purposive sampling method. The data analysis technique used in this study is multiple regression. Testing the regression with the assumptions used in testing the hypothesis that the classical assumption test (normality, multicollinearity, and heteroscedasticity), test the feasibility of the model, and the coefficient of determination. The results of this study indicate that there aren’t significant cash flow, profitability, firm size and firm risk on dividend policy and there is the effect of liquidity on dividend policy.Keywords: cash flow, liquidity, profitability, firm size ,firm risk, dividend policy.